Patient and Physician Satisfaction with Analgesic Treatment: Findings from the Analgesic Treatment for Cancer Pain in Southeast Asia (ACE) Study - Dang Huy Quoc Thinh; Wimonrat Sriraj; Marzida Mansor; Kian Hian Tan; Cosphiadi Irawan; Johan Kurnianda; Yen Phi Nguyen; Annielyn Ong-Cornel; Yacine Hadjiat; Hanlim Moon; Francis O. Javier (Pain Research and Management)
Aim. The aim of this study was to examine patients’ and physicians’ satisfaction, and concordance of patient-physician satisfaction with patients’ pain control status. Methods. This cross-sectional observational study involved 465 adults prescribed analgesics for cancer-related pain from 22 sites across Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam. Pain intensity, pain control satisfaction, and adequacy of analgesics for pain control were documented using questionnaires. Results. Most patients (84.4%) had stage III or IV cancer. On a scale of 0 (no pain) to 10 (worse pain), patients’ mean worst pain intensity over 24 hours was 4.76 (SD 2.47). More physicians (19.0%) than patients (8.0%) reported dissatisfaction with patient’s pain control. Concordance of patient-physician satisfaction was low (weighted kappa 0.36; 95% CI 0.03–0.24). Most physicians (71.2%) found analgesics to be adequate for pain control. Patients’ and physicians’ satisfaction with pain control and physician-assessed analgesic adequacy were significantly different across countries (P<0.001 for all). Conclusions. Despite pain-related problems with sleep and quality of life, patients were generally satisfied with their pain control status. Interestingly, physicians were more likely to be dissatisfied with patients’ pain control. Enhanced patient-physician communication, physicians’ proactivity in managing opioid-induced adverse effects, and accessibility of analgesics have been identified to be crucial for successful cancer pain management. This study was registered at ClinicalTrials.gov (identifier NCT02664987).